2017
DOI: 10.33160/yam.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Oxidative Stress, Physical Activity, and Vitamin Intake in Patients with Asthma

Abstract: Background Oxidative stress plays an important role in the pathogenesis of bronchial asthma. Antioxidant nutrition and supplementation have been used to reduce oxidative stress. However, a clinical trial with antioxidant supplementation showed no beneficial effects in patients with asthma. On the other hand, physical activity is related to the prognosis of chronic obstructive pulmonary disease (COPD) and is also related to oxidant status. We investigated the relationships between oxidative stress, serum levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A total of 17 studies explored correlates (k = 13) [ 19 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 51 , 52 , 53 ] or determinants (k = 6) [ 22 , 41 , 43 , 46 , 47 , 48 , 50 ] of physical activity or sedentary behaviour; most (82%) were of cross-sectional design ( Table 2 ). Of the 17 studies, 10 (59%) assessed physical activity or sedentary behaviour with pedometers or accelerometer devices ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 17 studies explored correlates (k = 13) [ 19 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 51 , 52 , 53 ] or determinants (k = 6) [ 22 , 41 , 43 , 46 , 47 , 48 , 50 ] of physical activity or sedentary behaviour; most (82%) were of cross-sectional design ( Table 2 ). Of the 17 studies, 10 (59%) assessed physical activity or sedentary behaviour with pedometers or accelerometer devices ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one of four studies found a statistically significant correlation between physical activity and QoL [ 53 ]. Studies that assessed the correlation between physical activity and eosinophils [ 22 , 48 , 51 , 53 ], Immunoglobulin E (IgE) [ 51 ], and markers of oxidative stress [ 45 ] did not find statistically significant results. However, associations with physical activity were found for high-sensitivity C-reactive protein (r 2 = 0.15) [ 22 , 48 ] and fractional concentration of exhaled nitric oxide (FeNo) (r = −0.37, p = 0.005) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigorous PA is particularly more effective in strengthening cardiorespiratory fitness [ 22 ] compared with moderate activity; however, no study has confirmed its effect by evaluating vigorous PA in adolescents. Additionally, in this field, large-scale research is necessary for proactive healthcare for adolescents [ 23 ]. Thus, this study analyzed the association between vigorous PA and stress in adolescents with asthma using the data from a large-scale survey of Korean adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Zn has beneficial roles in respiratory epithelium: as an antioxidant, anti-inflammatory agent, antiapoptotic agent, cofactor for DNA synthesis .Se has a crucial role in the inflammatory asthmatic process with the ability to affect the adhesion molecules expression. 7 Severity of airflow limitation, its reversibility, variability and confirmation of asthma can be assessed by measurement of lung function. Spirometry (FEV 1 %) is the most commonly and widespread acceptance methods to assess airflow limitation.…”
Section: Introductionmentioning
confidence: 99%